Impact of lymph node management on resectable non-small cell lung cancer patients - Apichat Tantraworasin (2018)
Background: A surgical lung resection with systematic mediastinal lymph node (LN) dissection is recommended by the National Comprehensive Cancer Network guideline. However, the effective number of dissected LNs, stations and positivity is still controversial. The aim of this study is to identify the impact of total numbers, LN stations and positivity of dissected LNs on tumor recurrence and overall death in resectable non-small cell lung cancer (NSCLC). Methods: This prognostic study used a retrospective data collection design. Adult patients with clinical resectable NSCLC who underwent pulmonary resection and mediastinal lymphadenectomy at Chiang Mai University between June 2000 and June 2012 were enrolled in this study. A multilevel mixed-effects parametric survival model was used to identify the effect of numbers, LN stations and positivity of dissected LNs to tumor recurrence and mortality. Results: The average number of dissected LNs was 22.7±12.8. Tumor recurrence was found in 51.3% and overall mortality was 43.3%. The number of dissected LNs was a prognostic factor for tumor recurrence [HR 0.98, 95% confidence interval (CI): 0.96-0.99]. There was a significant difference at the cut-pointed value of 11 dissected LNs for tumor recurrence (HR 2.22, 95% CI: 1.26-3.92). Dissection less than 11 nodes and less than 5 stations indicated a poor prognostic factor for tumor recurrence: for 3-4 stations (HR 3.01, 95% CI: 1.22-7.42) and for 1-2 stations (HR 1.96, 95% CI: 1.04-3.72). The positivity of dissected LNs was also a prognostic factor for tumor recurrence and overall mortality (HR 1.01, 95% CI: 1.01-1.02 and HR 1.01, 95% CI: 1.01-1.03, respectively). Conclusions: Eleven or more LN dissection with at least 5 stations influenced recurrent-free survival. Systematic LN dissection (SLND) should be performed not only to identify the positivity of dissected LNs but also to determine an accurate tumor nodal stage. A larger cohort should be further conducted to support these findings.